Intranodal injection of semimature monocyte-derived dendritic cells induces T helper type 1 responses to protein neoantigen - Gilliet, Michel; Schadendorf, Dirk (Blood, 2003)
Dendritic cells (DCs) represent the most potent antigen-presenting cells of the immune system capable of initiating primary immune responses to neoantigens. Here we characterize the primary CD4 T-cell immune response to protein keyhole limpet hemocyanin (KLH) in 5 metastatic melanoma patients undergoing a tumor peptide–based dendritic cell vaccination trial. Monocyte-derived dendritic cells displaying a semimature phenotype, as defined by surface markers, were loaded ex vivo with antigen and injected intranodally at weekly intervals for 4 weeks. All patients developed a strong and long-lasting delayed-type hypersensitivity reactivity to KLH, which correlated with the induction of KLH-dependent proliferation of CD4 T cells in vitro. Secondary in vitro stimulation with KLH showed significant increase in interferon-γ and interleukin-2 (IL-2) but not IL-4, IL-5, nor IL-10 secretion by bulk T cells. On the single-cell level, most TH1 cells among in vitro–generated KLH-specific T-cell lines confirmed the preferential induction of a KLH-specific type 1 T helper immune response. Furthermore, the induction of KLH-specific antibodies of the IgG2 subtype may reflect the induction of a type 1 cytokine profile in vivo after vaccination. Our results indicate that intranodal vaccination with semimature DCs can prime strong, long-lasting CD4 T-cell responses with a TH1-type cytokine profile in cancer patients.